Flexural crack propagation in steel fibre concrete beam / Nur Anisa Athirah Rosli - Rosli, Nur Anisa Athirah; Hamzah, Siti Hawa; Tengku Azhan, Tengku Aizzat Danial (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
The inclusion of steel fibres in the concrete matrix is the best alternative to control crack propagation along the failure plane. For decades, some of the studies carried out on steel fibre reinforced concrete beam (SFRC) had highlighted the effect of fibre dosage, fibre type and fibre size towards the mechanical behaviour of concrete, however, there are still uncertainties as to what extent does hooked end fibres with size of 35 mm and 60 mm at 40 kg/m3 and 80 kg/m3 respectively affected the flexural strength and crack produced in concrete. Thus, this study intends to investigate both effect of fibre dosage and fibre length of hooked end steel fibre towards flexural strength and crack propagation in 75 mm x 75 mm x 300 mm fibred concrete beam. In the study, hooked end steel fibres were incorporated into 12 beams having specified strength of 30 MPa. Meanwhile, the flexural strength of concrete was tested using Universal Testing Machine (UTM) under three point bending test. The incorporation of fibre at higher dosage with longer length has resulted in better results in terms of flexural strength and the crack produced as compared to the usage of short fibre at lower dosage